2017
DOI: 10.3390/su9060997
|View full text |Cite
|
Sign up to set email alerts
|

Are Crowdsourced Datasets Suitable for Specialized Routing Services? Case Study of OpenStreetMap for Routing of People with Limited Mobility

Abstract: Nowadays, Volunteered Geographic Information (VGI) has increasingly gained attractiveness to both amateur users and professionals. Using data generated from the crowd has become a hot topic for several application domains including transportation. However, there are concerns regarding the quality of such datasets. As one of the most famous crowdsourced mapping platforms, we analyze the fitness for use of OpenStreetMap (OSM) database for routing and navigation of people with limited mobility. We assess the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…The application of demographic and socioeconomic indicators has also revealed that OSM data completeness is affected by both population density (Zielstra & Zipf, ) and the income levels of contributors (Neis, Zielstra, & Zipf, ), while Camboim et al () have also shown that road completeness in urban areas is moderately well correlated with population density. The application of contributor indicators also led Mobasheri, Sun, Loos, and Ali () to the conclusion that the total number of OSM users has a direct impact on sidewalk information volume in these products. Most previous assessments have, however, been based on conceptual descriptions or qualitative analyses; for example, Camboim et al () demonstrated the presence of a correlation between road completeness and population density, but did not investigate how the latter could be utilized to quantitatively estimate the former, while Gröchenig, Brunauer, and Rehrl () qualitatively classified the completeness of OSM datasets into three phases encompassing “start,” “growth,” and “saturation” based on an analysis of dataset historical activity but did not quantify the completeness (e.g., between 60 and 80%) of each phase.…”
Section: Introductionmentioning
confidence: 99%
“…The application of demographic and socioeconomic indicators has also revealed that OSM data completeness is affected by both population density (Zielstra & Zipf, ) and the income levels of contributors (Neis, Zielstra, & Zipf, ), while Camboim et al () have also shown that road completeness in urban areas is moderately well correlated with population density. The application of contributor indicators also led Mobasheri, Sun, Loos, and Ali () to the conclusion that the total number of OSM users has a direct impact on sidewalk information volume in these products. Most previous assessments have, however, been based on conceptual descriptions or qualitative analyses; for example, Camboim et al () demonstrated the presence of a correlation between road completeness and population density, but did not investigate how the latter could be utilized to quantitatively estimate the former, while Gröchenig, Brunauer, and Rehrl () qualitatively classified the completeness of OSM datasets into three phases encompassing “start,” “growth,” and “saturation” based on an analysis of dataset historical activity but did not quantify the completeness (e.g., between 60 and 80%) of each phase.…”
Section: Introductionmentioning
confidence: 99%
“…Fan [35] used "development of building count over time" which was also based on analyzing the historical data in OSM. Mobasheri et al [36] analyzed the OSM sidewalk data by counting the number of road segments with/without a tag. Recently, Zhou [37] proposed using OSM building density as a proxy indicator to quantitatively estimate OSM building completeness.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hendawi point out the proliferation of volunteered geographic information (VGI) such as GPS tracks donated by individuals via forums such as OpenStreetMap has created an opportunity for providing next generation routing services [22]. Mobasheri proved crowdsourced datasets are suitable for specialized routing services [23]. Graser pointed out that the quality of these data sources and OpenStreetMap, in particular, is sufficient for answering questions about the heterogeneous nature of VGI in general [24].…”
Section: Introductionmentioning
confidence: 99%